miR-199a-5p regulatesHIF-1αandOSGIN2and its expression is correlated to soft-tissue sarcoma patients' outcome - Kessler, Jacqueline; Rot, Swetlana; Bache, Matthias; Kappler, Matthias; Wurl, Peter; Vordermark, Dirk; Taubert, Helge; Greither, Thomas (Oncology Letters, 2016)
Soft tissue sarcomas are a heterogeneous group of malignant neoplasms of mesenchymal origin. Partly due to hypoxia, an aggressive and radioresistant phenotype frequently develops, resulting in poorer patient outcome. microRNAs (miRNAs) are tiny, non-coding regulators of gene expression and in situations of cellular stress situations may predict clinical progression and patient outcome. In the present study, hypoxia-associated miR-199a-5p expression in 96 soft tissue sarcoma samples was analysed by reverse transcription-quantitative polymerase chain reaction and associations between miR-199a-5p expression and patient clinicopathological characteristics and survival were measured. Additionally, luciferase reporter assays analyzed the post-transcriptional regulation of hypoxia-associated genes hypoxia-inducible factor 1α (HIF-1α), oxidative stress induced growth inhibitor 2 (OSGIN2) and vascular endothelial growth factor (VEGF) by miR-199a-5p. Survival analyses indicated that low expression of miR-199a-5p was significantly correlated with poorer tumor-specific survival (univariate Cox's-Regression analyses; relative risk=1.92, P=0.029). Furthermore, it was demonstrated that the 3'UTR ofHIF-1α andOSGIN2genes were regulated by miR-199a-5pin-vitro, although the 3'UTR ofVEGFwas not. To the best of our knowledge, this is the first report demonstrating the regulation of the 3'untranslated region of theOSGIN2gene by miR-199a-5p and a significant correlation between low miR-199a-5p expression and a poor outcome of patients with soft tissue sarcoma.
EVALuna2:33568